1997
DOI: 10.1007/s004210050283
|View full text |Cite
|
Sign up to set email alerts
|

Relative exercise intensity of long-distance marching (120 km in 4 days) in 153 subjects aged 69?87 years

Abstract: The aim of this study was to determine the relative exercise intensity (oxygen uptake during the march/maximal oxygen uptake, VO2march/VO2max) during a long-distance march in subjects or over 70 years of age. Secondly, the effect of hypertension, cardiovascular and pulmonary diseases on the relative exercise intensity was evaluated. One hundred and fifty-three subjects, 97 men aged 76.7 (4.6) years and 56 women aged 72.8 (3.6) years who completed the 1993 Nijmegen day long-distance march (30 km x day(-1) on 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Running performance is influenced by several physiological variables, which can explain the decline in running performance with age. Most important are maximum aerobic capacity (VO 2max ), muscle function, strength, and lactate threshold [8, 13, 15, 17]. Aging is associated with a decline in muscle mass, which becomes progressive beyond the age of 50 [2, 4, 11, 13, 24, 25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Running performance is influenced by several physiological variables, which can explain the decline in running performance with age. Most important are maximum aerobic capacity (VO 2max ), muscle function, strength, and lactate threshold [8, 13, 15, 17]. Aging is associated with a decline in muscle mass, which becomes progressive beyond the age of 50 [2, 4, 11, 13, 24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…In earlier work we showed that even (training for) long distance marches may decrease the rate of decline of VO 2max with advancing age [16, 17]. Moreover, regular exercise is associated with a significant better physical function, improved cognition, a significant decrease in mortality and a better quality of life [2, 10, 12, 1822].…”
Section: Introductionmentioning
confidence: 99%